The influence of soft-tissue volume grafting on the maintenance of peri-implant tissue health and stability - Karina Obreja; Ausra Ramanauskaite; Amira Begic; Maria Elisa Galarraga-Vinueza; Puria Parvini; Frank Schwarz (SpringerOpen, 2021)
Abstract Background To investigate the influence of soft-tissue volume grafting employing autogenous connective tissue graft (CTG) simultaneous to implant placement on peri-implant tissue health and stability. Material and methods This cross-sectional observational study enrolled 19 patients (n = 29 implants) having dental implants placed with simultaneous soft-tissue volume grafting using CTG (test), and 36 selected controls (n = 55 implants) matched for age and years in function, who underwent conventional implant therapy (i.e., without soft-tissue volume grafting). Clinical outcomes (i.e., plaque index (PI), bleeding on probing (BOP), probing depth (PD), and mucosal recession (MR)) and frequency of peri-implant diseases were evaluated in both groups after a mean follow-up period of 6.15 ± 4.63 years. Results Significant differences between test and control groups at the patient level were noted for median BOP (0.0 vs. 25.0%; p = 0.023) and PD scores (2.33 vs. 2.83 mm; p = 0.001), respectively. The prevalence of peri-implant mucositis and peri-implantitis amounted to 42.1% and 5.3% in the test and to 52.8% and 13.9% in the control group, respectively. Conclusion Simultaneous soft-tissue grafting using CTG had a beneficial effect on the maintenance of peri-implant health.